INTEGRATION OF PASTURE, FODDER AND CATTLE IN COCONUT SMALL HOLDINGS - L V K Liyanage; H P S Jayasundera; D T Mathes; D N S Fernando (International Coconut Community Journal, 1989)
A farming system was established in a 45 year old coconut plantation at Rathmalagara Estate, Madampe, in the North Western Province of Sri Lanka. The main objective of this study was to evaluate the performance of an integrated farming system in relation to coconut production and productivity of land. Results inclicate that there has been no adverse effect on coconut and copra production clue to the establishment of the integrated system. The substitution of inorganic fertilizer mainly nitrogen and partly phosphorus and potassium through the integration of animals, fodder and pasture system did not affect the critical levels of nutrients in coconut leaves of treatment plots. Furthermore, feed supply through pasture/fodder in the system was adequate for cattle throughout. In terms of animal performance the average live weight gains were 306 g/head/day at the end of the first year. The most remarkable feature was that the integrated system reduced the cost of inorganic fertilizer for coconut by 69%, thus reducing the cost of production of coconut. Based on the overall results it is suggested that the integrated system is more productive and beneficial than a monoculture system to coconut small holdings.